Growth inhibitory properties of extracts prepared from selected Leptospermum and Melaleuca species against a panel of pathogenic bacteria - Mpala, Lindiwe Nomathemba; Chikowe, Getmore Rumbudzai; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Leptospermum longifolium (C.T. White & W.D. Francis) S.T. Blake, Leptospermum petersonii Bailey and Melaleuca alternifolia (Maiden & Betche) Cheel are aromatic native Australian trees with uses as traditional medicines. Essential oils produced from leaves of these species have reputed antiseptic properties against many bacteria. Despite this, L. longifolium, L. petersonii and M. alternifolia leaf solvent extractions have not been rigorously examined for antibacterial properties against many pathogens. Methods: The antimicrobial activity of methanolic L. longifolium, L. petersonii and M. alternifolia leaf extracts was investigated by disc diffusion and growth time course assays against a panel of pathogenic bacteria. The growth inhibitory activity was quantified by MIC determination. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: The methanolic L. longifolium, L. petersonii and M. alternifolia leaf extracts inhibited the growth of a wide range of bacterial species. Growth of both gram positive and gram negative bacteria was inhibited by all extracts. The L. longifolium and L. petersonii extracts were generally more potent inhibitors of bacterial growth than was the M. alternifolia extract against most bacterial species. A. hydrophilia, C. freundi, P. mirabilis and B. cereus growth was particularly susceptible to the extracts, with MIC values as low as 147 µg/mL (inhibition of A. hydrophilia growth by the L. longifolium extract). The antibacterial activity of the L. longifolium, L. petersonii and M. alternifolia extracts were further investigated by growth time course assays, with significant growth inhibition recorded in all cultures within 1 h of exposure. All extracts were determined to be nontoxic in the Artemia franciscana nauplii bioassay, indicating their safety for therapeutic uses. Conclusions: The lack of toxicity of the methanolic L. longifolium, L. peter- sonii and M. alternifolia leaf extracts and their growth inhibitory bioactivity against a panel of pathogenic bacteria partially validate Australian Aboriginal usage of these species as antiseptic agents and indicate their potential in the development of antiseptic agents.
Keywords: Myrtaceae; Leptospermum longifolium; Leptospermum peter- sonii; Melaleuca alternifolia; Tea-tree; Australian plants; Antibacterial activity; Medicinal plants